Effect of operating variables and kinetics of the lipase catalyzed transesterification of ethylene carbonate and glycerol - Gutierrez Lazaro, Ana; Velasco, Daniel; Boldrini, Diego Emmanuel; Yustos, Pedro; Esteban, Jesús; Ladero, Miguel (Fermentation)
Glycerol carbonate (GC) is a value-added product originating from the valorization of widely available glycerol (Gly), a side stream from the production of biodiesel. Here we approach the production of this chemical comparing two reactions based on the transesterification of Gly with dimethyl carbonate (DMC) and ethylene carbonate (EC). For the former reaction, it was observed that the free enzyme CALB (lipase B from Candida antarctica) gave the best results, whereas for the latter, Eversa Transform (a genetic modification of Thermomyces lanuginosus lipase) performed better than the rest. With the selected catalysts, their immobilized analogous enzymes Novozym 435 and Lypozyme TL IM, respectively, were also tested. Observing that the yields for the reaction with EC were significantly faster, other operating variables were evaluated, resulting the best performance using a closed system, tert-butanol as solvent, a concentration of enzyme Eversa Transform of 3 % w/w, a molar excess of EC:Gly of 9:1 and a temperature of 60 C. Finally, several runs were conducted at different temperatures and molar ratios of EC:Gly, fitting a kinetic model to all experimental data for the reaction catalyzed with Eversa Transform. This model included the bimolecular transesterification reaction of Gly and EC catalyzed by the lipase and a reversible ring-opening polymerization of EC. Fil: Gutierrez Lazaro, Ana. Complutense University of Madrid; España Fil: Velasco, Daniel. Complutense University of Madrid; España Fil: Boldrini, Diego Emmanuel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina Fil: Yustos, Pedro. Complutense University of Madrid; España Fil: Esteban, Jesús. Max Planck Institute for Chemical Energy Conversion. Molecular Catalysis Division; Alemania Fil: Ladero, Miguel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro ...